ANALYSIS OF SERVICE QUALITY AND FACILITIES TOWARDS TOURIST SATISFACTION AT VILLA MARI PRO LAU KAWAR - Akbar, Rizki Al; Satria, Januar Budi; Nasution, Novita Aulia Sari; Winata, Edi (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
ourism is an activity managed by various organizations and services provided by the community, business actors, and both central and regional governments. Tourism refers to travel undertaken by both individuals and groups of people. by studying the uniqueness of tourist attractions visited during a certain period of time, personal goals, personal development, or learning. Service and institutional quality at this point are more important in the tourism business because they are thought to influence visitor satisfaction. Villa Mari Pro Lau Kawar, located at the foot of Mount Sinabung, is one of the tourist destinations that is widely visited by tourists. This study aims to analyze how much service facilities affect the level of visitor satisfaction at Villa Mari Pro Lau Kawar. The method applied in this study is descriptive with a quantitative approach. Secondary data is obtained by collecting relevant theories, reports, and documentation, and primary data is obtained by data collection techniques, namely conducting observations, interviews, and distributing questionnaires to tourists or respondents and collecting them back. The number of samples used is 95 people. Data processing is carried out using descriptive statistical methods and multiple linear regression. The research findings show that the quality of services and facilities has a significant influence on visitor satisfaction.